A spatial analysis on seismo-ionospheric anomalies observed by DEMETER during the 2008 M8.0 Wenchuan earthquake. (15th December 2015) - Liu, J.Y.; Chen, Y.I.; Huang, C.C.; Parrot, M.; Shen, X.H.; Pulinets, S.A.; Yang, Q.S.; Ho, Y.Y.
Highlights: Box-and-whisker plots find anomalies appearing before 2008 M8.0 Wenchuan earthquake. The DEMETER electron density and ion density are useful to detect earthquake precursors. A spatial analysis is essential to confirm the observed anomalies related to the earthquake. Abstract: This paper examines seismo-ionospheric anomalies (SIAs) observed by the French satellite DEMETER (Detection of Electro-Magnetic Emissions Transmitted from Earthquake Regions) during the 12 May 2008 M8.0 Wenchuan earthquake. Both daytime and nighttime electron density (Ne), electron temperature (Te), ion density (Ni) and ion temperature (Ti) are investigated. A statistical analysis of the box-and-whisker method is utilized to see if the four DEMETER datasets 1–6 days before and after the earthquake are significantly different. The analysis is employed to investigate the epicenter and three reference areas along the same magnetic latitude discriminating the SIAs from global effects. Results show that the nighttime Ne and Ni (daytime Ti) over the epicenter significantly decrease (increase) 1–6 days before the earthquake. The intersections of the global distribution of the significant differences (or anomalous changes) in the nighttime Ne, the nighttime Ni, and the daytime Ti 1–6 days before and after the earthquake specifically appear over the epicenter, which strongly suggests that DEMETER observes SIAs of the 2008 M8.0 Wenchuan earthquake.